PENYELESAIAN KONFLIK KEPEMILIKAN TANAH “DALAM KAJIAN HISTORIS KASUS RE-EGENDOM KE ULAYAT DI GAMPONG GAJAH MEUNTAH KEC. SUNGAI RAYA KAB. ACEH TIMUR - Imam Hadi Sutrisno; Bachtiar Akob; T. Hasan Basri (Global Science Society, 2020)
Cases of land ownership conflicts often occur in Aceh, sometimes even pose a serious threat to the management of plantation companies, both private and state-owned. This threat is no joke, so the very undesirable thing is the release and transfer of ownership to the total community. The people of Gajah Meuntah Village are villagers who have lived for years mixed with plantation ownership of PT. Patria Kamou. It is difficult to distinguish which property belongs to the garden and which belongs to the village. The community believes that their lands and villages were stolen by the plantations in 1988, with PT. Gajah Meuntah became PT. Patria Kamou. Citizens' movement as a form of struggle began in 2010 but has always been stymied. After the period ended December 31, 2013, the turmoil emerged with extraordinary power, namely demanding re-egendom to the communal land. The negotiations were initiated by the Langsa Regional Police Station, and subsequently measured by the Aceh Regional Office in 2015, accompanied by the YARA Team.